Peer Reviewer - Effect of Avocades to LDL Cholesterol as a Preventive Risk of Atherosclerosis - Rahman, Sp.PD., Finasim, Dr. dr. Shahrul (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
International Journal of Multidisciplianary and Current Research